Suppressive effects of Streptococcus thermophilus KLDS 3.1003 on some foodborne pathogens revealed through in vitro, in vivo and genomic insights. Issue 7 (10th July 2020) - Evivie, Smith Etareri; Ogwu, Matthew Chidozie; Abdelazez, Amro; Bian, Xin; Liu, Fei; Li, Bailiang; Huo, Guicheng
Abstract : Foodborne diseases (FBDs) remain a persistent global challenge and recent research efforts suggest that lactic acid bacteria (LAB) strains can contribute towards their prevention and treatment. Abstract : Foodborne diseases (FBDs) remain a persistent global challenge and recent research efforts suggest that lactic acid bacteria (LAB) strains can contribute towards their prevention and treatment. This study investigates the genetic properties of Streptococcus thermophilus KLDS 3.1003 as a potential probiotic and health-promoting LAB strain as well as its in vitro and in vivo activities against two foodborne pathogens. In vitro, its antimicrobial activities and tolerance levels in simulated bile salts and acids were determined. The cytotoxic effects of the LAB strain in RAW264.7 cells were also evaluated. For in vivo evaluation, 24 BALB/c mice were orally administered control and trial diets for 14 days. Genomic analyses of this strain's bacteriocin configuration, stress response system and multidrug resistance genes were annotated to validate in vitro and in vivo results. In vitro antimicrobial results show that the cells and CFS of S. thermophilus KLDS 3.1003 could inhibit both pathogens with the former being more effective ( P < 0.05). In addition, its cell-free supernatant (CFS) could inhibit the growth of both pathogens, with catalase treatment having the highest effect against it. More so, after 3 h of incubation, survivability levels of S. thermophilus KLDS 3.1003 were significantly high ( P < 0.05). LPS-induced RAW264.7 cell activities were also significantly reduced by 10 8 –10 9 CFU mL −1 of S. thermophilus KLDS. In vivo, significant weight losses were inhibited in the TSTEC group compared to the TSTSA group ( P < 0.05). Moreover, pathogen-disrupted blood biochemical parameters like HDL, LDL, TP, TG, AST, ALT and some minerals were restored in the respective prevention groups (TSTEC and TSTSA ). Genomic analyses showed that S. thermophilus KLDS 3.1003 has bacteriocin-coding peptides, which accounts for its antimicrobial abilities in vitro and in vivo . S. thermophilus KLDS 3.1003 is also endowed with intact genes for acid tolerance, salt-resistance, cold and heat shock responses and antioxidant activities, which are required to promote activities against the selected foodborne pathogens. This study showed that S. thermophilus KLDS 3.1003 has the genomic capacity to inhibit foodborne pathogens' growth in vitro and in vivo, thus qualifying it as a potential probiotic, antimicrobial and bio-therapeutic candidate.